On urban fear: privilege, symbolic violence, topophobia: the everyday experiences of middle-class women in Secunda, South Africa - Paquet, Tarryn Nicole Kennedy (School of Architecture, Planning and Geomatics, 2018)
I consider how the nature and meaning of space shape middle-class women's topophobia in the new town of Secunda (with a particular focus on symbolic violence). In Lefebvre's 'terrorist societies' fear becomes latent as citizens seek to maintain status quos which maintain systems of privilege. I demonstrate that one such system is white privilege. Secunda assists in maintaining these systems as its design draws heavily on Eurocentric values and new town 'best practices'. As a company town developed in reaction to international sanctions during apartheid, its design also resulted in the preservation of certain privileged groups. I argue that white privilege is a white problem and thus base my study on the (white) middle-class as a dominant group. I show that the identities of women (although traditionally viewed as passive and fearful) are diverse, falling both victim to and inflicting symbolic violence and topophobia. I focus on topophobia, or spatial fear, as fear affects us all and influences our shaping of urban space. The mutually reinforcing nature (abstract representations of the ideologies of planners) and meaning (infused through emotions, identities and power relations) of space are explored. I dispute the bias against emotion-based research that exists within planning, arguing that this has debilitating consequences for transformation. I suggest the use of intersecting emotion-spectra rather than the dichotomous approach conventionally taken by emotion research. A feminist ethnography is used with an iterative inductive research process engaging a variety of techniques, including digital/social media. My own multiple insider identities (of middle-class, white, English-Afrikaans woman, and planner) are used to critique systems of dominance. Findings highlight various forms of symbolic violence (in addition to white privilege) including codes of 'respectability' and 'purity', consumerism, fat talk, and persistent gender roles. Further, possible influences of dominant systems on space (particularly in reinforcing persistent social segregation in Secunda) are demonstrated. Symbolic violence can be used to deflect accountability, but this research shows that topophobia is a planning problem, worthy of consideration.